(3GdCeGf ef CNWGQ GdCSaGQ hGdCReGfs - (3GdWGhSj, GdMSfj, CHh GdbGSe, QVi GdnqOjf, Ydj Hf ehSi Hf LYaQ Hf WGhhS, J (B664 (3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg GdPj GSJLGQJ Hg GdCQhGM HdSGf GdMGd (B... (3hHYO aEfj hLOJ GafSGf eSGaQG eP NQL Edi GdhLhO aj XghQ GdBHGA hGdLOhO(B... (3hCSejJg(B... (3hCLYdg CHhGHG hcd HGH jTJed Ydi aUhd(B...s
(3BNQgG (B:s
(3bO PcQfG ef GdBOGH aj gPg GdNeSI efGRd eG CfTCfGg HMSH eG fYJbO Cfg ehGab dWGYI Gddg (B... (3adPdc GbJUQfG Ydi gPG GdebOGQ hajg caGjI dPj GdHUGFQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, U(B26s
(3GdPQjYI HQbe(B: 1365s
(3cTa GdXfhf(B: (3L(B1(3, U(B66s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs